Faktor Risiko Stres Emosional pada Mahasiswa Kedokteran tahun Pertama Universitas Andalas di Masa Pandemi COVID-19 - Mar’atul Fadhilah; Arina Widya Murni; Amel Yanis (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Emotional stress is a psychological reaction due to stressors that can be detrimental, whether physical, mental or emotional stimuli that tend to disrupt the function of the organism which can activate the organism's flight or fight reaction. The COVID-19 pandemic situation is a new stressor for first year medical students because they immediately face the transition period of learning to online so they have to adapt to the new learning system. The aim of the research was to determine the risk factors that trigger emotional disorders in first year medical students at Andalas University class of 2020 during the COVID-19 pandemic. This study implemented a cross-sectional design. The subjects of this research were first year medical students at Andalas University. The measurement instruments used were the DASS-42 and the Holmes and Rahe Stress Scale for Youth. The total number of medical students who experienced stress from a total sample of 225 was 74 people (32.9%). The risk factor for student stress in this study was the learning process (69 people). Factors that aggravate academic stress were the death of family members/other family members/partners/close friends. The factor that relieves academic stress was vacation. The p value for the analysis of the relationship between stress levels and risk factors was >0.05 (not significant). It was concluded that the risk factor for emotional stress for medical students class of 2020 at Andalas University during the COVID-19 pandemic was the academic atmosphere.Keywords: medical students; first year; risk factors; stress ABSTRAK Stres emosional adalah reaksi psikologis akibat stressor yang dapat merugikan, baik stimulus fisik, mental, ataupun emosional yang cenderung mengganggu fungsi organisme yang dapat mengaktifkan reaksi  flight or fight oleh organisme tersebut. Situasi pandemi COVID-19 merupakan  stressor baru bagi mahasiswa kedokteran tahun pertama karena langsung menghadapi masa transisi pembelajaran menjadi daring sehingga mereka harus beradaptasi dengan sistem pembelajaran baru. Tujuan penelitian adalah untuk mengetahui faktor risiko pencetus timbulnya gangguan emosi mahasiswa kedokteran Universitas Andalas tahun pertama angkatan 2020 di masa pandemi COVID-19. Penelitian ini menerapkan desain cross-sectional. Subjek penelitian ini ialah mahasiswa kedokteran tahun pertama Universitas Andalas. Instrumen pengukuran yang digunakan adalah DASS-42 dan Holmes and Rahe Stress Scale for Youth. Total mahasiswa kedokteran yang mengalami stres dari total sampel 225 adalah sebanyak 74 orang (32,9%). Faktor risiko stres mahasiswa pada penelitian ini ialah proses pembelajaran (69 orang). Faktor yang memperberat stres akademik tersebut ialah kematian anggota keluarga/anggota keluarga lain/pasangan/teman dekat. Faktor yang meringankan stres akademik ialah liburan. Nilai p unuk analisis hubungan antara tingkat stres dengan faktor risikonya adalah >0,05 (tidak signifikan). Disimpulkan bahwa faktor risiko stres emosional mahasiswa kedokteran angkatan 2020 Universitas Andalas di masa pandemi COVID-19 ialah faktor suasana akademik.                         Kata kunci: mahasiswa kedokteran; tahun pertama; faktor risiko; stres